Presence of Society of Pharmacology in the Department of Pharmacy: A Leading Step to Promote Pharmacology - Naveed Ullah (Open Journal of Pharmacology and Pharmacotherapeutics - Peertechz Publications, 2016)
The Society is a form of charity which will have a task to advance and encourage the entire spectrum of Pharmacology and may leads the way in research and appliance of Pharmacology throughout the world. Focus made recently in the Department of Pharmacy, University of Swabi on the current point, and a society have been developed for the betterment of Pharmacology/ drug knowledge at Department level, University level and at the Global community. The detailed aims and objective have been discussed which may concluded to the betterment of health, awareness about drugs, easy to gain knowledge by the Pharmacy students, to minimize toxic and unwanted effects of the drugs, potency and effi cacy of the drugs and most importantly to promote Pharmacology, which is a major, major and major subject in the field of health, Pharmacy and medical sciences.